THE IMPACT OF SOCIAL NETWORKS ON THE DEVELOPMENT OF COLLABORATIVE COMPETENCE OF UNIVERSITY STUDENTS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The rapid development of digital technologies and the widespread use of social networks have significantly transformed the educational environment in higher education institutions. Social networks, which were initially designed for communication and entertainment, are increasingly being integrated into the academic sphere, serving as effective platforms for collaborative learning and competence development. This article examines the impact of social networks on the formation and enhancement of collaborative competence among university students. Collaborative competence is considered as the ability of students to work effectively in teams, share knowledge, solve problems collectively, and achieve common goals through mutual support and interaction. The study highlights that the use of social networks such as Telegram, Facebook, Instagram, and specialized educational platforms fosters student engagement in academic discussions, improves the exchange of ideas, and creates opportunities for joint project development. Moreover, social networks allow students to break traditional barriers of time and space, enabling continuous communication and collaborative activities beyond the classroom. This, in turn, contributes to the development of critical thinking, digital literacy, communication skills, and leadership qualities. However, the article also discusses challenges associated with the use of social networks in educational contexts, such as distraction, misinformation, superficial interaction, and the potential risk of reduced face-to-face communication skills. To address these issues, the article emphasizes the importance of integrating social networks into a structured pedagogical framework, where instructors play an active role in guiding students’ activities and ensuring that online collaboration remains purposeful and academically productive. The findings suggest that social networks, when properly managed and integrated into higher education curricula, have a positive and transformative effect on the development of collaborative competence among students. They not only serve as tools for communication but also as interactive learning environments that prepare future specialists to work in team-oriented, digitally driven professional contexts. Thus, the strategic use of social networks in education can be seen as an innovative approach to strengthening students’ collaborative competence and overall academic performance.